1975
DOI: 10.23986/afsci.71858
|View full text |Cite
|
Sign up to set email alerts
|

Content fo copper, zinc, lead, cadmium and mercury in muscle, liver and kidney of Finnish cattle

Abstract: A total of 120 normal slaughter cows were analyzed with respect to Cu, Zn, Pb, Cd and Hg in muscle, liver and kidney. The cows orginated from 6 different slaughter-houses throughout the country. Imported cow livers, represented by 10 samples from Australia, 10 from Poland and 15 from Ireland, were also analyzed for comparison with the Finnish material. The Cu content in the Finnish animals turned out to be relatively low. The imported samples had even lower contents. There seemed to be no correlation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…Lead is stored mainly in the liver and kidney, and normal muscle lead value appears to be much lower than that reported in these tissues (Doyle and Spaulding, 1978). Other studies gave same results as in the study done by Stabel-Tancher et al (1975) which showed that lead concentration was 0.12 mg/kg in muscle of Finnish cattle, 0.28 mg/kg in liver and 0.26 mg/kg in kidney, in addition to the study performed by Kottferova and Korenekova (1995) which presented the same results. Results reported in this study were in agreement with those reported above as mean lead concentrations in livers and kidneys were significantly higher (p<0.05) than that recorded in muscles (Table 1).…”
Section: Resultssupporting
confidence: 75%
“…Lead is stored mainly in the liver and kidney, and normal muscle lead value appears to be much lower than that reported in these tissues (Doyle and Spaulding, 1978). Other studies gave same results as in the study done by Stabel-Tancher et al (1975) which showed that lead concentration was 0.12 mg/kg in muscle of Finnish cattle, 0.28 mg/kg in liver and 0.26 mg/kg in kidney, in addition to the study performed by Kottferova and Korenekova (1995) which presented the same results. Results reported in this study were in agreement with those reported above as mean lead concentrations in livers and kidneys were significantly higher (p<0.05) than that recorded in muscles (Table 1).…”
Section: Resultssupporting
confidence: 75%
“…A number of reports show that the elemental composition of tissues is affected by age. Stabel-Taucher et al (1975) reported that the concentration of Pb in liver and kidney of cattle was age dependent and that it accumulated in greater quantities in the kidneys than in the liver. Friberg et al (1973) reported similar data for the accumulation of Cd in both animals and humans.…”
Section: Physiological Factorsmentioning
confidence: 99%